The Potential of Renminbi as an International Currency and its Implications - Wang, Can (2012)
The purpose of the paper is to explore the determinants of an international currency, evaluate the potential of the RMB to be an international currency, provide policy advice, and discuss the implications of the RMB internationalising. After the current financial crisis, the defect of one currency dominance has been exposed and the multi-currency system is expected to be established to diversify the foreign exchange reserve holdings. Given that China overtook Japan and became the world’s second largest economy in 2010 and its significant role in global trade, its currency the renminbi (RMB) emerges as a potential international currency. Because of benefits being an international currency, this promotion is desirable in China. Efforts have been made especially in the offshore market Hong Kong in recent years. However, there are also risks lying ahead as the financial system in China is still defective. The process of internationalising the RMB mainly depends on the pace of liberalising its capital account and releasing restrictions on its domestic financial market, which is determined by authorities’ consideration associated with benefits and risks. Simulations show that if the RMB could be fully convertible it will gradually become an international currency in region.